The Eighth Dialog System Technology Challenge - Kim, Seokhwan; Galley, Michel; Gunasekara, Chulaka; Lee, Sungjin; Atkinson, Adam; Peng, Baolin; Schulz, Hannes; Gao, Jianfeng; Li, Jinchao; Adada, Mahmoud; Huang, Minlie; Lastras, Luis; et al. (Third NeurIPS workshop on Conversational AI: “Today's Practice and Tomorrow's Potential”, 2019)
This paper introduces the Eighth Dialog System Technology Challenge. In line with recent challenges, the eighth edition focuses on applying end-to-end dialog technologies in a pragmatic way for multi-domain task-completion, noetic response selection, audio visual scene-aware dialog, and schema-guided dialog state tracking tasks. This paper describes the task definition, provided datasets, and evaluation set-up for each track. We also summarize the results of the submitted systems to highlight the overall trends of the state-of-the-art technologies for the tasks.